Tempo de trabalho e trabalho no tempo: a dialética das (des)integrações no trabalho pedagógico de pedagogos(as) no Instituto Federal Farroupilha - Cezar, Taise Tadielo (2021)
This study is part of the research carried out by Kairós - Study and Research Group on Labour, Education and Public Policies, at UFSM/RS. It aimed and dialectically to study the movements of the subjects expressed in documents, in the production and in the journeys carried out by pedagogues at the Instituto Federal Farroupilha, analysing the mediations that are established in the multiple times experienced during the pedagogical work they produce at the Institution. The theoretical and methodological approach that guided the data production and analysis process was in the field of Historical-Dialectical Materialism. The stage of data production took place through a previous questionnaire, documentary research and systematic observation carried out in eight admirable units of IFFar. Consequently, the analysis process took place, considering a systematization in the following study categories: institutional structure, division, and production of the pedagogues’ work, working hours, times lived. These made it possible to analyse dialectically the movements and mediations between working time, pedagogical work, and the dialectics of decays. From the study carried out understood that the movements of these education workers are contradictorily constituted during an objective time, through which they experience subjective production processes in the event of their praxis. Thus, mediations are established that are evident in the institutionality of the subjects' working time and work, this corresponds to a legal and administrative plan that materializes in the practice of pedagogues as they experience the production of pedagogical work. At different and varied times during the working days in the federal public service in Professional and Technological Education (EPT), a movement that composes the historicity of the pedagogues in the Institution, individually and collectively. Therefore, it is defended in the context of capitalist society, such movements and mediations are expressed as the Dialectic of Decay, explained under the contradictory manifestations and effects of the movements of integration, non-integration, and disintegration between the times, works and the pedagogues as such, under the conditions of being IFFAR field education workers.